Implementation and evaluation of a pharmacist-led hypertension management service in primary care: outcomes and methodological challenges - Bajorek B; LeMay KS; Magin P; Roberts C; Krass I; Armour CL (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: Suboptimal utilisation of pharmacotherapy, non-adherence to prescribed treatment, and a lack of monitoring all contribute to poor blood (BP) pressure control in patients with hypertension. Objective: The objective of this study was to evaluate the implementation of a pharmacist-led hypertension management service in terms of processes, outcomes, and methodological challenges. Method: A prospective, controlled study was undertaken within the Australian primary care setting. Community pharmacists were recruited to one of three study groups: Group A (Control - usual care), Group B (Intervention), or Group C (Short Intervention). Pharmacists in Groups B and C delivered a service comprising screening and monitoring of BP, as well as addressing poor BP control through therapeutic adjustment and adherence strategies. Pharmacists in Group C delivered the shortened version of the service. Results: Significant changes to key outcome measures were observed in Group C: reduction in systolic and diastolic BPs at the 3-month visit (P<0.01 and P<0.01, respectively), improvement in medication adherence scores (P=0.01), and a slight improvement in quality of life (EQ-5D-3L Index) scores (P=0.91). There were no significant changes in Group B (the full intervention), and no differences in comparison to Group A (usual care). Pharmacists fed-back that patient recruitment was a key barrier to service implementation, highlighting the methodological implications of screening. Conclusion: A collaborative, pharmacist-led hypertension management service can help monitor BP, improve medication adherence, and optimise therapy in a step-wise approach. However, blood pressure screening can effect behaviour change in patients, presenting methodological challenges in the evaluation of services in this context.